Analisa Hasil Pengujian Resistor Filem Karbon 4 Gelang Warna dan Metal Filem Resistor 5 Gelang Warna - Fransiskus Seda; Yustinus Sanda Bungin Ada (Publikasi Indonesia, 2025)
The rapid development of technology today has a significant impact, especially in the field of education, especially for students who are not able to carry out measurements of electronic components, such as resistors of four and five color bracelets. This study was conducted on 10 resistors of four color bracelets and 10 resistors of five color bracelets to determine the value of resistance, voltage, and current in each resistor. The measurement results of the carbon film resistor show the lowest resistance value of 47? and the highest 56,000?. Meanwhile, in the five-color bracelet film metal resistor, the lowest resistance value is 1? and the highest is 3,300?. In voltage analysis, the four-band resistor produces the lowest voltage of 18.6 mV and the highest of 220.5 mV, while the five-band resistor of the color bracelet produces the lowest voltage of 210 mV and the highest of 220.9 mV. For current analysis, the color four-band resistor has a lowest current of 0.003 mA and a highest of 220 mA, while a color bracelet resistor has a lowest current of 0.1 mA and a highest of 4.7 mA. This measurement and analysis is expected to help technicians and students majoring in Electrical Engineering in understanding the value of resistance, voltage, and current on four and five color bracelet resistors in Basic Electronics lectures.